Tabiat kemeruapan perubahan harga getah asli Malaysia - Zaidi Isa,; Norhayati Abdul Jamil, (Penerbit Universiti Kebangsaan Malaysia, 2004)
This study presents the trend of volatility in natural rubber price of Malaysia for Ribbed Smoked Sheet Grade 1 (RSS 1) and Standard Malaysian Rubber Grade 20 (SMR 20). The price changes in RSS 1 and SMR 20 indicate that the empirical distributions have heavy tails and sharp peaks at the center compared to the normal distributions. In addition,the variance underlying these price variables may be varying over time. Therefore, the data cannot be modeled as standard time series model with assumption variance is constant over time. Alternatively, ARCH and GARCH model were used. One of the parts that many researchers are interested is the asymmetry (leverage effect) in the variance. In this study, this part has been captured by two model of the ARCH family: the EGARCH and GJRGARCH. Result indicates that both EGARCH and GJR-GARCH models did not generally support asymmetry in the pattern of volatility of both RSS 1 and SMR 20. After comparing of these four models, it can be shown that the GARCH (1,1) model fit to data very satisfactorily.